2017
DOI: 10.1007/s00792-016-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy of an extremely halophilic microbe: technical aspects

Abstract: Most halophilic Archaea of the class Halobacteriaceae depend on the presence of several molar sodium chloride for growth and cell integrity. This poses problems for structural studies, particularly for electron microscopy, where the high salt concentration results in diminished contrast. Since cryo-electron microscopy of intact cells provides new insights into the cellular and molecular organization under close-to-live conditions, we evaluated strategies and conditions to make halophilic microbes available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Furthermore, more cell–cell bridges would probably have been observed in a medium containing a higher salt concentration, as mating efficiency was shown to be higher at high salt concentrations (3.4 M NaCl), which is most likely caused by an altered S-layer glycosylation ( Guan et al, 2012 ; Shalev et al, 2017 ). Since previous studies in Halobacterium salinarum showed that higher salt concentrations reduced the contrast of electron micrographs ( Bollschweiler et al, 2017 ), images were obtained from cells grown in a medium containing 2.4 M NaCl where optimal growth was still observed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more cell–cell bridges would probably have been observed in a medium containing a higher salt concentration, as mating efficiency was shown to be higher at high salt concentrations (3.4 M NaCl), which is most likely caused by an altered S-layer glycosylation ( Guan et al, 2012 ; Shalev et al, 2017 ). Since previous studies in Halobacterium salinarum showed that higher salt concentrations reduced the contrast of electron micrographs ( Bollschweiler et al, 2017 ), images were obtained from cells grown in a medium containing 2.4 M NaCl where optimal growth was still observed.…”
Section: Discussionmentioning
confidence: 99%
“…A pioneering work from (Marko et al, 2006) showed the proof-of-principle that a new non-mechanical approach -using a focused-ion-beam -can be used to prepare thin vitreous sections in prokaryotes. In 2009 we developed the cryo-FIB technology for single cells on EM-grids (Bäuerlein, 2010;Rigort and Bäuerlein et al, 2012) that is now used as a routine preparation-technique for in-situ cryo-TEM studies in eukaryotes and prokaryotes (Arnold et al, 2016;Asano et al, 2015;Böck et al, 2017;Bollschweiler et al, 2017;Engel et al, 2015bEngel et al, , 2015aFukuda et al, 2017;Hagen et al, 2015;Jasnin et al, 2016;Mahamid et al, 2016;Pfeffer et al, 2017;Schaffer et al, 2015) as well as in this work (Bäuerlein et al, 2017).…”
Section: Opening Windows Into the Cell: Cryo-fibmentioning
confidence: 99%
“… 2016 ), especially as technical limitations due to the high salt concentrations have been partially overcome (Bollschweiler et al. 2017 ). Moreover, the expansion of available tools for in vitro studies will aid to address basic questions related to the energetics of protein transport.…”
Section: Discussionmentioning
confidence: 99%